What would the expression 3*x* + 7 be when x = 3?
Simplify 5*x*^{2} + 7*x* – 2(*x*^{2} + *x*).

When x = 3, 3*x* + 7 = 3 × 3 + 7 = 9 + 7 = 16.

5*x*^{2} + 7*x* – 2(*x*^{2} + *x*)
= 5*x*^{2} + 7*x* – 2*x*^{2} – 2*x*
= (5 – 2)*x*^{2} + (7 – 2)*x*
= 3*x*^{2} + 5*x*
= *x*(3*x* + 5)

First we check the bracket.
That cannot be simplified.
We multiply the contents of the brackets by the number 2.
Note that the minus sign applies to both terms that we get from this.
Next we collect together like terms.
Finally, we take out the common factor *x*.

To Martin Bland's M.Sc. index.

This page maintained by Martin Bland.

Last updated: 2 October, 2007.